Atividades Antifúngica e Toxicológica In Silico dos Enantiômeros (R)-(+)- e (S)-(-)-citronelal - Medeiros, Cássio Ilan Soares (2016)
The incidence of vulvovaginal fungal infections has increased dramatically over the last decades, therefore being the second most common cause of vulvovaginal candidiasis (VVC) placed after bacterial vaginosis diagnosed in 40% of the women with vaginal discharge. The increasing resistance of micro-oganismos pathogens to existing antimicrobial market has driven the search for new therapeutic alternatives, such as natural herbal products belonging to various families of the plant kingdom, such as Poaceae and Myrtaceae, which are presented as a viable solution due to the low cost and easy access of the population. Highlighted, the genus Cymbopogon and the Eucalyptus plants is one of the main sources of biologically active molecules, among them the monoterpenes holds a huge biological potential of human interest. However, the research of plant-derived compounds with pharmacological properties must always be attached to toxicity studies in order to show the absence of these substances harm to the human body. Given this context, it has studied the biological activity of enantiomers (R)-(+)- and (S)-(-)-citronellal against C. albicans and C. tropicalis strains derived from in vitro vulvovaginal secretions, as well as the parameters toxicological to predict the theoretical oral toxicity in silico. To achieve the antimicrobial in vitro studies; determination of minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) was used microdilution test. Also it was applied to disk diffusion technique on solid medium for comparative study of antifungal resistance/sensitivity profile used in the treatment of vulvovaginal candidiasis isolated and associated with monoterpenes studieds. The MIC's and MFC's of the (R)-(+)- and (S)-(-)-citronellal to 90% of fungal strains were respectively (R)MIC90% 16μg/mL and (R)MFC90% 32μg/mL; (S)MIC90% 64μg/mL and (S)MFC90% 128μg/mL (Strong antifungal activity against C. albicans and C. tropicalis). Were observed high resistance of C. albicans to fluconazole and itraconazole 12 (92.30%) strains. However, this resistance was reversed in 9 (75%) and 7 (58.33%) respectively, when combined with (R)-(+)-citronellal and 6 (50%) in combination with (S)-(-)-citronellal. Furthermore, it was also observed C. tropicalis high resistance to amphotericin B, itraconazole and miconazole. However, the resistance was reversed to amphotericin B and itraconazole, as a result of the synergistic effect in 2 (66.65%) of yeast. For miconazole resistance was reversed in 3 (100%) of the strains for both enantiomers. In the in silico analysis, both enantiomers have good oral bioavailability theoretically, however, a potential irritant was observed as possible toxic effect on these monoterpenes. In conclusion, these results suggest that the (R)-(+)- and (S)-(-)-citronellal have antimicrobial effect, and which also exert effect modifier activity when antifungal agents in combination. However, although presenting good oral bioavailability theoretically, the varied toxicological profile suggests the need to assess the risk-benefit of this compound in the production of a new antifungal drug, by conducting in vivo trials.